Native country of the heart: A memoir - Moraga, Cherríe (Picador, 2019)
"This memoir's beauty is in its fierce intimacy." –Roy Hoffman, The New York Times Book ReviewOne of Literary Hub's Most Anticipated Books of 2019From the celebrated editor of This Bridge Called My Back, Cherríe Moraga charts her own coming-of-age alongside her mother’s decline, and also tells the larger story of the Mexican American diaspora.Native Country of the Heart: A Memoir is, at its core, a mother-daughter story. The mother, Elvira, was hired out as a child, along with her siblings, by their own father to pick cotton in California’s Imperial Valley. The daughter, Cherríe Moraga, is a brilliant, pioneering, queer Latina feminist. The story of these two women, and of their people, is woven together in an intimate memoir of critical reflection and deep personal revelation. As a young woman, Elvira left California to work as a cigarette girl in glamorous late-1920s Tijuana, where an ambiguous relationship with a wealthy white man taught her life lessons about power, sex, and opportunity. As Moraga charts her mother’s journey―from impressionable young girl to battle-tested matriarch to, later on, an old woman suffering under the yoke of Alzheimer’s―she traces her own self-discovery of her gender-queer body and Lesbian identity, as well as her passion for activism and the history of her pueblo. As her mother’s memory fails, Moraga is driven to unearth forgotten remnants of a U.S. Mexican diaspora, its indigenous origins, and an American story of cultural loss.Poetically wrought and filled with insight into intergenerational trauma, Native Country of the Heart is a reckoning with white American history and a piercing love letter from a fearless daughter to the mother she will never lose.
Keywords: 1900-1999; amériques; approches et analyses; chicanas; histoire et politique; histoire familiale; identités LGBTQIA2+; mexique; mémoire collective; personnes lesbiennes; périodes historiques; queer; régions géographiques; thématiques; états-unis

This bridge called my back: Writings by radical women of color - Moraga, Cherríe; Anzaldúa, Gloria (SUNY Press., 2015)
merged in the last quarter of the twentieth century. Through personal essays, criticism, interviews, testimonials, poetry, and visual art, the collection explores, as coeditor Cherríe Moraga writes, the complex confluence of identities–race, class, gender, and sexuality–systemic to women of color oppression and liberation. Reissued here, forty years after its inception, this anniversary edition contains a new preface by Moraga reflecting on Bridge's living legacy and the broader community of women of color activists, writers, and artists whose enduring contributions dovetail with its radical vision. Further features help set the volume's historical context, including an extended introduction by Moraga from the 2015 edition, a statement written by Gloria Anzaldúa in 1983, and visual art produced during the same period by Betye Saar, Ana Mendieta, Yolanda López, and others, curated by their contemporary, artist Celia Herrera Rodríguez. Bridge continues to reflect an evolving definition of feminism, one that can effectively adapt to and help inform an understanding of the changing economic and social conditions of women of color in the United States and throughout the world.
Première édition 1981. Les textes "La Guëra" de Cherríe L. Moraga et « Lesbianism As an Act of Resistance » de Clark, Cherryl ont été donné en lecture au cours POL4212.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; arts; cours; cycles supérieurs; discipline; fem1000; fem7000; femmes* de couleur; histoire et politique; intersectionnalité; lit3220; littérature; pol4212; pratiques féministes; premier cycle; privilèges; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; témoignage; états-unis; études littéraires

« Réfugiées d’un monde en feu ». Avant-propos à la deuxième édition, 1983 - Moraga, Cherríe L. (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2011)
Trois années sont passées et j’essaie de m’imaginer à quoi ressemble la nouvelle lectrice ou le nouveau lecteur de Bridge. Qu’avez-vous besoin de savoir ? J’ai entendu à travers des lettres et lors de mes voyages, que le livre avait aidé à changer l’esprit de certaines personnes (et, je l’espère, également leur cœur), mais personne n’aura été plus transformé par ce livre que les femmes ayant contribué à son existence. Il a provoqué un changement tellement fondamental dans ma vie qu’aujourd’hu...
Keywords: amériques; approches et analyses; cours; fem1300; féminisme décolonial; inégalités; premier cycle; queer; racisme; ressource en ligne; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; violences